2012
DOI: 10.1074/jbc.m111.299099
|View full text |Cite|
|
Sign up to set email alerts
|

Specific Armadillo Repeat Sequences Facilitate β-Catenin Nuclear Transport in Live Cells via Direct Binding to Nucleoporins Nup62, Nup153, and RanBP2/Nup358

Abstract: Background:The nuclear localization of ␤-catenin is directly linked to its cancer causing activity. Results: Armadillo repeats (10 -12) mediate nuclear transport of ␤-catenin through direct interaction with specific nuclear pore complex proteins. Conclusion: ␤-Catenin can function like a nuclear transport receptor in its ability to translocate independently through the nuclear pore complex. Significance: ␤-Catenin may transport specific binding partners between the nucleus and cytoplasm in response to Wnt sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 54 publications
(66 reference statements)
2
62
0
Order By: Relevance
“…Although APC (and axin) was proposed to mediate the nuclear export of b-catenin (Bienz, 2002), there is strong evidence that bcatenin can freely diffuse into and out of the nucleus (Fagotto et al, 1998;Kose et al, 1997;Wiechens and Fagotto, 2001;Henderson and Fagotto, 2002;Sharma et al, 2012), and that APC and other binding partners of b-catenin all negatively affect bcatenin translocation (Krieghoff et al, 2006). Our observation of very fast transport kinetics further corroborates the notion of selective diffusion, and the analysis of transport in APC-depleted cells confirms that APC is not required for translocation.…”
Section: Apc and B-catenin Nuclear Transportsupporting
confidence: 75%
See 2 more Smart Citations
“…Although APC (and axin) was proposed to mediate the nuclear export of b-catenin (Bienz, 2002), there is strong evidence that bcatenin can freely diffuse into and out of the nucleus (Fagotto et al, 1998;Kose et al, 1997;Wiechens and Fagotto, 2001;Henderson and Fagotto, 2002;Sharma et al, 2012), and that APC and other binding partners of b-catenin all negatively affect bcatenin translocation (Krieghoff et al, 2006). Our observation of very fast transport kinetics further corroborates the notion of selective diffusion, and the analysis of transport in APC-depleted cells confirms that APC is not required for translocation.…”
Section: Apc and B-catenin Nuclear Transportsupporting
confidence: 75%
“…5). The import and export kinetics in parental SW480 cells were roughly similar to those measured in HEK293 and NIH 3T3 cells (Krieghoff et al, 2006;Sharma et al, 2012). However, the use of the spinning-disk confocal microscope allowed us to obtain information about the initial phase of recovery, which had not been studied so far.…”
Section: Direct Binding To Apc Is Required For B-catenin Phosphorylationmentioning
confidence: 71%
See 1 more Smart Citation
“…c-Met, the tyrosine kinase receptor of HGF has been linked to -catenin signaling [379,380] and it has been shown that HGF/c-Met can activate -catenin signaling independent from Wnt signaling [381] at the site of E-cadherin containing junctions. Binding of HGF to c-Met triggers an autophosphorylation at Tyr1234 and Tyr1235, which in turn mediates a tyrosine kinasemediated Tyr654 and Tyr670 phosphorylation of -catenin [382] inducing the dissociation of -catenin from E-cadherin [352,383]. Similarly, Tyr142 and Tyr654 phosphorylation by the FLT3/ITD kinase (Fms-like Tyrosine Kinase-3) leads to a dissociation ofcatenin from its complex with E-cadherin [344,384].…”
Section: Other Transmembrane Receptors Influencing Wnt/ -Catenin Signmentioning
confidence: 99%
“…A recent study also indicates ARM domains 10-12 of the C-terminal tail of β-catenin to be active in the bidirectional transport activity when bound to specific nuclear pore complex (NPC) components [54]. Therefore, we predict that RPL37a might play another role in inhibiting migration of β-catenin within the cell.…”
Section: Rpl37a/ctnnb1 (Pdb Id: 2z6h)mentioning
confidence: 99%